Co-operation and conflict between firms, communities, new social movements and the role of government the Cerro de San Pedro case - Hernández, José G. Vargas (Interações, 2016)
The aim of this paper is to analyze relationships of cooperation and conflict between a mining company andthe involved communities, New Social Movements and the three levels of government. The mining company begunoperations for an open pit mine of gold and silver supported by officials from the local, state and federal government.The inhabitants of these communities supported by environmental groups and NGOs argue that the project willpollute sources of fresh water besides of perturbing the environment and the ecology of the region.